STRUCTURAL EQUATION MODEL OF ARTICLES COVID-19 ON SOCIAL MEDIA TO HEALTH LITERACY AND BEHAVIOR AMONG HEALTH INFORMATION STUDENTS - Evina Widianawati; Widya Ratna Wulan; Ika Pantiawati (Jurnal Riset Informatika, 2021)
The COVID-19 infodemic is spreading through social media and website requires people to be able to evaluate information during a pandemic. Health literacy is the key to evaluating the infodemic and to get the decision making on health behavior. Health information students primarily use digital technologies such as social media to get information about covid-19 so that students need to have good health literacy to evaluate infodemic. The purpose of this study was to determine the effect of covid-19 article content on health literacy and health behavior among health information students. Data were collected using a questionnaire on 142 health information students then analyzed descriptively and using the structural equation modeling (SEM) method. The results of the descriptive analysis show that 70% of students access covid-19 information through social media mainly using Instagram, where more than half of students access covid-19 article content <= once a day by reading and liking the article. Based on the results of SEM, it is known that the most important factor of the article content is trustworthy content, the most important factor of health literacy is adherence to prevention and the most important factor of health behavior is reducing contact with other people. From the results of the SEM effect test, it is known that there is a direct effect of content articles on health literacy of 51%. On the other hand, there is a direct effect from health literacy to health behavior of 63,4% and there is no significant effect from content articles to health behavior.